PELATIHAN PEMBELAJARAN KETERAMPILAN PADA GURU- GURU SMP KETERAMPILAN SE-KOTA YOGYAKARTA - Martono, Martono (Universitas Negeri Yogyakarta, 2010)
The training was started from the problems of the weaknesses of teachers' competence in developing craft design and skills on teaching strategy aimed for the students. Based on that problem, the teachers asked for an instructional skill training to develop the design insight, the teaching strategy, and the work of arts as a scientific work. This training was aimed to develop the knowledge and the skill of craft design by utilizing various materials, forming techniques and its instruction method for the students, to know the craft product produced by the craft teachers in Junior High School, to give knowledge for the craft teachers of junior high school in describing the work of arts as scientific work. The training method used was a presentation to deliver the knowledge of the development of craft design, craft instruction, and description of the work of arts as scientific work. The demonstration method was used to explain the production process of craft made from the gypsum by molding technique. The presentation method by the participants of the training was to be able to take the responsibility of the result of the craft, the craft instructional strategy applied in schools, and the presentation of arts description as scientific work. The teachers who participated could join the training well and they could understand the material given by the trainer team. The teachers could make some work of craft and they could apply it in the instruction by using the method they choose in the school well. Most of them are weak in developing craft design which is covered for the need of student instructions based on the development of the students. The work of craft made by the teachers can be used as the instructional media to work on arts as well as scientific work. The teachers apply the instructional method by observing, imitating, and modificating to make work of arts. The example given by model as the instructional media is not merely to be imitated but it is also to motivate the students in doing the work of arts. The teachers make the description of work of arts as the scientific work gave quite a good result. The description of the work of craft is used to develop the competence and the improvement of the teacher's career in the future